Physical activity improves outcomes of combined lenvatinib plus anti-PD-1 therapy in unresectable hepatocellular carcinoma: a retrospective study and mouse model - Xue-Feng Liu; Xiao-Dong Zhu; Long-Hai Feng; Xiao-Long Li; Bin Xu; Kang-Shuai Li; Nan Xiao; Ming Lei; Hui-Chuan Sun; Zhao-You Tang (Experimental Hematology & Oncology, 2022)
Abstract Background Physical activity is known to have anti-cancer effects, including immunomodulatory actions. This study investigated the hypothesis that physical activity synergizes with combined lenvatinib plus anti-PD-1 therapy to enhance efficacy in patients with unresectable HCC. Methods The physical activity levels of patients with unresectable HCC receiving combined lenvatinib plus anti-PD-1 therapy were recorded by questionnaire. Patients were categorized according to physical activity levels (active vs. sedentary). The primary outcome was overall survival (OS). Secondary outcomes included objective response rate (ORR) and progression-free survival (PFS). A subcutaneous syngeneic HCC model was generated in C57BL/6 mice. Mice were randomized to receive placebo, combined lenvatinib plus anti-PD-1 antibodies or combination therapy plus physical activity. Tumors were measured every 3 days and harvested for immunohistochemistry analysis at 20 mm maximum diameter. Results Fifty-nine patients with unresectable HCC were categorized to active (n = 28) or sedentary (n = 31) groups. The active group had higher albumin and des-γ-carboxy prothrombin levels and lower hepatitis B virus load at baseline; other clinical and oncologic characteristics were comparable between the two groups. Patients in the active group had significantly longer OS (HR = 0.220, 95% CI 0.060–0.799) and PFS (HR = 0.158, 95% CI 0.044–0.562) and higher ORR (OR = 4.571, 95% CI 1.482–14.102) than patients in the sedentary group. Regular physical activity was independently associated with OS, PFS and ORR. The mouse model showed that physical activity significantly suppressed tumor growth and prolonged survival of tumor-bearing mice. Furthermore, physical activity inhibited Treg cell infiltration and immune checkpoint expression (including CTLA4, TIGIT and TIM3) induced by long-term combined lenvatinib plus anti-PD-1 therapy, improving efficacy. Conclusions Regular physical activity was associated with improved outcomes in unresectable HCC receiving combined lenvatinib plus anti-PD-1 therapy. Physical activity may improve therapeutic efficacy by reprograming the tumor microenvironment from an immunosuppressive to immunostimulatory phenotype.